2016
DOI: 10.15171/ijhpm.2016.36
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Electronic Personal Health Records in Canada: Perceptions of Stakeholders

Abstract: Background: Healthcare stakeholders have a great interest in the adoption and use of electronic personal health records (ePHRs) because of the potential benefits associated with them. Little is known, however, about the level of adoption of ePHRs in Canada and there is limited evidence concerning their benefits and implications for the healthcare system. This study aimed to describe the current situation of ePHRs in Canada and explore stakeholder perceptions regarding barriers and facilitators to their adoptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 26 publications
3
68
0
1
Order By: Relevance
“…A review of the literature on factors affecting the acceptance and adoption of ePHRs by consumers in developed and developing countries indicated that some factors are relevant to both developed and developing countries [25][26][27]; these include technical, individual, environmental, and social factors [27]. Technical factors relate to the usability of the system or features that contribute to the feasibility of technology use, such as effort and performance expectancy of the offered technology.…”
Section: Hindrances and Drivers Of Ephr Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature on factors affecting the acceptance and adoption of ePHRs by consumers in developed and developing countries indicated that some factors are relevant to both developed and developing countries [25][26][27]; these include technical, individual, environmental, and social factors [27]. Technical factors relate to the usability of the system or features that contribute to the feasibility of technology use, such as effort and performance expectancy of the offered technology.…”
Section: Hindrances and Drivers Of Ephr Adoptionmentioning
confidence: 99%
“…They found privacy and security of ePHRs were of concern to 49% of respondents. Specifically, users were hesitant to embrace the system because it contains sensitive personal information that could be hacked [26,35,36]. Therefore, information security is of significant importance when adopting ePHRs, due to external threats of unauthorised access to private sensitive information.…”
Section: Privacy and Security Of Healthcare Consumersmentioning
confidence: 99%
“…Caregivers who assume an allied care giving role not recognized as health information custodian None 12. Gagnon, et al, 2016 Qualitative study Canadian service providers Not identified Electronic personal health records Use Access Disclosure Confidentiality Autonomy 1. Confusion, lack of awareness 2.…”
Section: Resultsmentioning
confidence: 99%
“…Factors related to organizations and their processes, specifically to staff relations that act either as barriers or facilitators of access and utilization of privacy of information rights, were identified at the meso level. Barriers included a persistent lack of willingness on the part of organizations to share their information databases in order to ease the stress on YADD and their families (Clement, & Obar, 2016 ; Desai, 2013 ; Dyke et al, 2016 ; Gagnon et al, 2016 ; Larivie’re-Bastien, & Racine, 2011 ; Peekhaus, 2008 ; Mills, et al, 2003 ; Ministry of Health and Long-Term care (MHLTC), 2006 ; Lacobucci, 2014 ; Urowitz et al, 2008 ) and lack of commitment to use of technological advances to protect information privacy rights (Mills, et al, 2003 ; Siegel et al, 2009 ; Urowitz et al, 2008 ). Throughout the review, YADD needs were found to be unrepresented in organizational processes (Austin, 2006 ; CACL, 2011 ; Clement, & Obar, 2016 ; Siegel et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar efforts have been underway for some time across multiple countries ( Ludwick & Doucette, 2009). While the potential advantages are substantial, the government ownership of data remains controversial (Gagnon et. al, 2016;Anderson, 2007).…”
Section: Whose Data Is It?mentioning
confidence: 99%